Socioeconomic inequality in timing of ANC visit among pregnant women in Ethiopia, 2019 - Kidie, Atitegeb Abera; Asmamaw, Desale Bihonegn; Belachew, Tadele Biresaw; Fetene, Samrawit Mihret; Baykeda, Tsegaw Amare; Endawkie, Abel; Zegeye, Alebachew Ferede; Tamir, Tadesse Tarik; Wubante, Sisay Maru; Fentie, Elsa Awoke; Negash, Wubshet Debebe; Addis, Banchilay (Frontiers in Public Health, 2024)
Background: antenatal care (ANC) remains an invaluable approach to preventive care for ensuring maternal and infant health outcomes. Women in sub-Saharan Africa make their first antenatal care ANC visits very late. In Ethiopia, only 20% of women had their first antenatal care ANC visits in the first trimester. Timely and appropriate antenatal care practices have life-saving potential for mothers and children. An understanding of socioeconomic inequality of the timing of early antenatal care ANC visit and its determinants may help contribute to tackling disparities and to achieve the Sustainable development goalsSDGs for maternal health.Objective: the aim of this study was to assess socioeconomic inequality in the timing of antenatal care ANC visit Method: a secondary data sourced from Mini Ethiopian demographic health survey 2019 was used for this study.and we used a health survey conducted in 2019. A total of 2906 pregnantreproductive aged women were included and concentration curves were used to show inequality among socio-demographic and economic variables. Decomposition analysis was done in order to estimate the contribution of each independent variable to inequality in the timing of antenatal care ANC visit.Result: the estimate of early initiation of antenatal care ANC was 63%. The concentration index was 0.18 (p-value <0.001). The inequality in timing of antenatal care ANC visit was more concentrated among the wealthiest pregnant women with a concentration index value of 0.18 (p<0.001). Based on decomposition analysis result, wealth index (81.9 %.), education status (22.29%) and region (0.0642%) of women were the contributing factors for inequality in timing of antenatal care ANC visit.Conclusion: wealth index, educational status and region were major significant contributors of inequality for early initiation of antenatal care ANC visit. Improving women's wealth, education and narrowing the inequality gap is very important for the improvement of the health status of women and their children. It should focus on interventions targeted at early antenatal care ANC visit on determinants of socio-economic inequities.